Control of land rights by foreign nationals through nominee agreements in Bali - Vania Melati; Winanto Wiryomartani (LEGAL BRIEF, 2022)
Property rights as the most absolute right that can be owned by a legal subject is something that is very important for the Indonesian nation. Land, as a basic need in carrying out life, has a social function designated and utilized for the greatest prosperity of the Indonesian people. On that basis, the ownership of the Freehold Land is only limited to Indonesian Citizens and some legal entities are excluded. This has created dissatisfaction for foreign nationals who wish to own land indefinitely in Bali, Indonesia. This dissatisfaction gave rise to the idea of carrying out legal smuggling through the practice called nominee agreements. This writing is intended to examine legal smuggling carried out through the nominee agreement, as well as the parties participating in the implementation of this legal smuggling.